A Critique of the Book "A Selection of Masterpieces of Arabic Literature in the First Abbasid Period " - Mohsen Seifi; Mahvash Hassanpoor (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book "A Selection of Masterpieces of Arabic Literature in the First Abbasid Period " written by Mirloohiis one of the works that the writer has selected, and the examples of prose and poetry of the first Abbasid era have been translated and analyzed. The study of the book shows that this work, while having concessions, is free of defects. This essay aims to observe the principles of critique, using a descriptive-analytic method to determine the extent of adherence of the author to the standards and rules of writing the critiques.  A careful review of the book suggests that this work has some shortcomings in content and form. Some of the most fundamental of which are as follows:  addressing unnecessary topics such as the poet's biography and neglecting some of the essential topics, such as the Abbasid era poetry. There are many typographical errors found in the book that could give the beginners inaccurate information and even mislead the readers.